1999
DOI: 10.1007/bf03343609
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes insipidus and increased serum levels of leptin and lactate-dehydrogenase (LDH) in an adolescent boy with a primary intracranial germinoma. Case Report and an endocrinological revaluation of literature

Abstract: A 16-year-old boy presented with a four-month history of polyuria-polydipsia and a diplopia which had reverted after treatment. The neuroimaging studies performed had been strongly suggestive of an optic nerve glioma, while endocrinological investigation (beta-hCG 420 IU/L) has lead to the correct diagnosis later confirmed at the immunohystochemical analysis performed at biopsy. The high serum level of hCG was unaffected by bromocriptine nor octreotide, while the PRL level (80.0 microg/L) was reduced only by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Only 2 out of 38 patients showed more than one endocrine abnormality. Hyperprolactinemia and secondary hypogonadism were the most frequent findings, although hyperprolactinemia is not specific for pituitary dysfunction (Carella et al, 1999). Postoperative assessment of endocrine functions showed that hyperprolactinemia, secondary hypogonadism and hypothyroidism resolved in most of the adult patients (Table 2), but not in children.…”
Section: Discussionmentioning
confidence: 98%
“…Only 2 out of 38 patients showed more than one endocrine abnormality. Hyperprolactinemia and secondary hypogonadism were the most frequent findings, although hyperprolactinemia is not specific for pituitary dysfunction (Carella et al, 1999). Postoperative assessment of endocrine functions showed that hyperprolactinemia, secondary hypogonadism and hypothyroidism resolved in most of the adult patients (Table 2), but not in children.…”
Section: Discussionmentioning
confidence: 98%